Pengaruh Kualitas Pelayanan Tokopedia terhadap Kepuasan Konsumen pada Pengguna Tokopedia di Surabaya - Sindi Kurnia Sari; Sonja Andarini (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
Currently, business development has led to the digital economy or online market due to changes in people's shopping styles, which have begun to shift from offline shopping to online shopping. This is an opportunity for business actors to market their products through digital media such as e-commerce. E-commerce facilitates communication between sellers and buyers, facilitates marketing and product promotion activities by sellers, facilitates the sale and purchase transaction process, facilitates payments made by consumers because it can be done online. This study was shown to analyze the effect of service quality on Tokopedia consumer satisfaction in Surabaya. The variables used in this study are service quality which consists of efficiency, system availability (reliability), fulfillment, confidentiality (privacy), responsiveness (responsiveness), compensation (compensation), contact (contact). And the variable of consumer satisfaction which consists of the suitability of expectations, loyalty, interest in visiting again and willingness to recommend. This study uses a survey method by distributing online questionnaires to 100 Tokopedia users in Surabaya. Based on the data analysis, it can be concluded that service quality has a positive and significant effect on Tokopedia consumer satisfaction in Surabaya.